Interaction effects on galaxy pairs with Gemini/GMOS - II: oxygen abundance gradients - Rosa, D. A. (2014)
In this paper we derived oxygen abundance gradients from HII regions located in eleven galaxies in eight systems of close pairs. Long-slit spectra in the range 4400-7300 Å were obtained with the Gemini Multi-Object Spectrograph at Gemini South (GMOS). Spatial profiles of oxygen abundance in the gaseous phase along galaxy disks were obtained using calibrations based on strong emission-lines (N2 and O3N2). We found oxygen gradients significantly flatter for all the studied galaxies than those in typical isolated spiral galaxies. Four objects in our sample, AM1219A, AM1256B, AM 2030A and AM2030B, show a clear break in the oxygen abundance at galactocentric radius R/R₂₅ between 0.2 and 0.5. For AM1219A and AM1256B we found negative slopes for the inner gradients, and for AM2030B we found a positive one. In all these three cases they show a flatter behaviour to the outskirts of the galaxies. For AM2030A, we found a positive-slope outer gradient while the inner one is almost compatible with a flat behaviour. A decrease of star formation efficiency in the zone that corresponds to the oxygen abundance gradient break for AM1219A and AM2030B was found. For the former, a minimum in the estimated metallicities was found very close to the break zone that could be associated with a corotation radius. On the other hand, AM1256B and AM2030A, present a SFR maximum but not an extreme oxygen abundance value. All the four interacting systems that show oxygen gradient breakes the extreme SFR values are located very close to break zones. Hii regions located in close pairs of galaxies follow the same relation between the ionization parameter and the oxygen abundance as those regions in isolated galaxies.